2009
DOI: 10.4162/nrp.2009.3.2.162
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns associated with hypertension among Korean males

Abstract: The objectives of this study were to identify the dietary patterns associated with hypertension among Korean males. Data from the 2001 Korean National Health and Nutrition Survey of 1,869 men aged 20-65 years were used for the analysis. As an initial analysis, a factor analysis was applied to identify major dietary patterns among the subjects. Then logistic regression analysis was conducted to identify the pattern related with hypertension. As a result of the initial analysis, three major dietary patterns were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 22 publications
5
17
0
1
Order By: Relevance
“…Our data may imply that the decreased risk of hypertension in the dairy and carbohydrate pattern may be related to increased calcium and potassium intake. A previous cross-sectional study based on the second KHANES of 1869 Korean men conducted in 2001 reported no significant correlations between dietary pattern and hypertension [46]. However, a recent cross-sectional study of 5308 Korean adults based on the 2007-2008 KHANES data indicated that the drinking dietary pattern was significantly associated with both hypertension and pre-hypertension [47].…”
Section: Discussionmentioning
confidence: 99%
“…Our data may imply that the decreased risk of hypertension in the dairy and carbohydrate pattern may be related to increased calcium and potassium intake. A previous cross-sectional study based on the second KHANES of 1869 Korean men conducted in 2001 reported no significant correlations between dietary pattern and hypertension [46]. However, a recent cross-sectional study of 5308 Korean adults based on the 2007-2008 KHANES data indicated that the drinking dietary pattern was significantly associated with both hypertension and pre-hypertension [47].…”
Section: Discussionmentioning
confidence: 99%
“…higher intakes of vegetables, potatoes, soya products, fruits, seaweeds, citrus, beans and dried fish) was associated with lower levels of SBP, DBP and pulse pressure in women (23) . In a previous cross-sectional study of 1869 Korean males aged 20-65 years, no significant association was observed between dietary patterns and hypertension prevalence (25) . However, we found that a drinking dietary pattern was significantly associated with hypertension in the Korean population.…”
Section: Discussionmentioning
confidence: 99%
“…In Western countries there is a positive association between 'Western' dietary patterns and hypertension (19)(20)(21)(22)(23) , although a null association has also been reported (24)(25)(26)(27)(28) . However, in Asia no significant association between a Western dietary pattern and hypertension was found in most existing studies (29)(30)(31)(32)(33)(34)(35)(36) , with a small number of studies showing a positive association between this pattern and hypertension (37)(38)(39)(40) . The Western dietary pattern contains processed foods, is low in fibre and has high amounts of refined carbohydrates, fat (especially saturated fat) and salt.…”
Section: Modern Dietary Pattern and Hypertensionmentioning
confidence: 99%